2016
DOI: 10.17269/cjph.107.5205
|View full text |Cite
|
Sign up to set email alerts
|

Immigrant status and having a regular medical doctor among Canadian adults

Abstract: OBJECTIVE: New immigrants generally arrive in Canada with a health advantage over their Canadian counterparts, but lose that advantage over time. Difficulties in acquiring a physician may contribute. Past studies relied on older data, and lacked control for many confounders and assessment of gender differences. We assessed the relationship between immigrant status and having a regular doctor among Canadian adults. METHODS:Cross-sectional data from the 2011-2012 Canadian Community Health Survey were self-report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…While established immigrants were more likely to have a regular health care provider than recent immigrants, there was no difference in the mean number of medical consultations in the past year of recent and established immigrants. These findings are consistent with the three previous studies that examined the effect of time since immigration on having a regular doctor and found that established immigrants were more likely to have a regular doctor than recent immigrants [ 5 , 8 , 9 ]. Previous secondary data analyses did not examine number of medical consultations in the past year as a measure of health care utilization.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…While established immigrants were more likely to have a regular health care provider than recent immigrants, there was no difference in the mean number of medical consultations in the past year of recent and established immigrants. These findings are consistent with the three previous studies that examined the effect of time since immigration on having a regular doctor and found that established immigrants were more likely to have a regular doctor than recent immigrants [ 5 , 8 , 9 ]. Previous secondary data analyses did not examine number of medical consultations in the past year as a measure of health care utilization.…”
Section: Discussionsupporting
confidence: 92%
“…The existing literature suggests that time since immigration is an important predictor for utilization of health care for Canadian immigrants [ 4 , 6 , 8 , 9 ], with established immigrants being more likely to have a regular doctor than recent immigrants. However, many studies of utilization of health care by immigrants in Canada did not include time since immigration in the analysis [ 6 , 7 , 10 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic has disproportionate health, social, and economic impacts on immigrants and racialized communities (Guttmann et al, 2020; Price-Haywood et al, 2020). Older adults within these communities are particularly vulnerable (Garcia et al, 2020) as they are more likely to have declining health, experience social isolation and loneliness, and report greater unmet health needs than the general population (Degelman & Herman, 2016; De Jong Gierveld et al, 2015; Koehn et al, 2013; Salma & Salami, 2020). Targeted and tailored strategies are required to support immigrant and racialized older adults impacted by the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Our finding of a gap in health service use among immigrants with diagnosed mental health disorders is consistent with previous studies. 16,[18][19][20][21][23][24][25][26] Gaps in health insurance coverage may impact access to services and influence future use and interactions with the Canadian health system. 36,37 Many provinces have a 3-month waiting period before new, landed immigrants are eligible for provincial health coverage 38 causing delays in seeking or accessing health services.…”
Section: Discussionmentioning
confidence: 99%
“…4,7,21,22 Immigrants report unmet care needs and may underuse health care services due to not knowing where to access health care services, the perception that they would receive inadequate care, transportation barriers, and language barriers. 23 Immigrants are also less likely to have a regular doctor 24 and more likely to visit urgent care or walk-in clinics or emergency departments for care. 25 Furthermore, emergency departments may be viewed as a more convenient place of care, 26 and immigrant children appear more likely to receive mental health care for the first time in the emergency department.…”
Section: Introductionmentioning
confidence: 99%